Association of Family Support with Treatment Adherence in Tuberculosis Patients - Agus, Al Ihksan; Rosmiati (Omni Health Journal, 2026)
Background: Tuberculosis (TB) remains a major public health problem that requires long-term treatment and sustained patient adherence. Non-adherence to TB therapy can lead to treatment failure and drug resistance, and is influenced by various factors, including family support as a key social determinant of health. Objective: To examine the association between family support and treatment adherence among tuberculosis (TB) patients. Methods: This quantitative observational study employed a cross-sectional design and was conducted among 120 pulmonary TB patients undergoing treatment at a primary health care facility. Data were collected using a family support questionnaire and a medication adherence scale (Morisky Medication Adherence Scale). Statistical analysis was performed using the Chi-square test with a significance level of p < 0.05. Results: The results showed that patients with good family support had significantly higher levels of medication adherence compared to those with poor family support (p < 0.05). Conclusion: Family support is significantly associated with treatment adherence in TB patients. These findings highlight the importance of incorporating family empowerment and involvement strategies into TB control programs to improve treatment adherence and outcomes.